2014
DOI: 10.1063/1.4871624
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent dynamics and logarithmic domain growth during the spinodal decomposition of a glass-forming liquid

Abstract: We use large-scale molecular dynamics simulations of a simple glass-forming system to investigate how its liquid-gas phase separation kinetics depends on temperature. A shallow quench leads to a fully demixed liquid-gas system whereas a deep quench makes the dense phase undergo a glass transition and become an amorphous solid. This glass has a gel-like bicontinuous structure that evolves very slowly with time and becomes fully arrested in the limit where thermal fluctuations become negligible. We show that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
149
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(165 citation statements)
references
References 78 publications
14
149
1
Order By: Relevance
“…A more recent work on a low density gel reported instead subdiffusive behaviour [37]. At a more coarse-grained level, it was suggested that localised bondbreaking events in gels may result in compressed exponentials [38], a mean-field scenario that was recently revisited using a mesoscopic elasto-plastic model for generic glassy materials [39], in which the gel structure however plays no direct role.Using large-scale numerical simulations of a particlebased model for gel formation [13,14], we show that the spontaneous microscopic aging dynamics during gelation possesses all anomalous signatures reported experimentally. We find a subdiffusive aging dynamics at short lengthscales, corresponding to caged particle motion inside the gel strands, crossing over to superdiffusive relaxation at larger lengthscales triggered by intermittent snapping of the fractal network.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A more recent work on a low density gel reported instead subdiffusive behaviour [37]. At a more coarse-grained level, it was suggested that localised bondbreaking events in gels may result in compressed exponentials [38], a mean-field scenario that was recently revisited using a mesoscopic elasto-plastic model for generic glassy materials [39], in which the gel structure however plays no direct role.Using large-scale numerical simulations of a particlebased model for gel formation [13,14], we show that the spontaneous microscopic aging dynamics during gelation possesses all anomalous signatures reported experimentally. We find a subdiffusive aging dynamics at short lengthscales, corresponding to caged particle motion inside the gel strands, crossing over to superdiffusive relaxation at larger lengthscales triggered by intermittent snapping of the fractal network.…”
mentioning
confidence: 99%
“…Using large-scale numerical simulations of a particlebased model for gel formation [13,14], we show that the spontaneous microscopic aging dynamics during gelation possesses all anomalous signatures reported experimentally. We find a subdiffusive aging dynamics at short lengthscales, corresponding to caged particle motion inside the gel strands, crossing over to superdiffusive relaxation at larger lengthscales triggered by intermittent snapping of the fractal network.…”
mentioning
confidence: 99%
See 3 more Smart Citations